PENGEMBANGAN SOFT SKILL DALAM PENDIDIKAN SEBAGAI BEKAL KEWIRAUSAHAAN - Setya Widyawati (Gelar : Jurnal Seni Budaya, 2011)
Directorate of Academic and Directorate of Institutional, Directorate-General of Higher Education  has launched Soft Skills Developing Program awarded on a competitive basis to the circle of  higher education. In this period of intense competition, the development of hard skills should be in  line with that of soft skills in higher education as an institution that turns out steadfast and excellent  human resources. To instill soft skills needs some exemplars, ranging from university leaders,  lecturers, and supporting staffs as the front liners who have direct contacts with students. If  students are accustomed to be treated well and respected, sooner or later they will be good servants  in society. This is meant by a simple transmission. The alternative transmissions of soft skills,  among others, are through 1) teaching method called Student Centre Learning (SCL) implemented  in teaching process by three ways, namely, Lecture role model, Message of the week, and Hidden  curriculum; 2) Student Extracurricular Activity Units covering spirituality, art, sports, and so on.  As the domain of emotional quotient, soft skills have an important role in entrepreneurial spirit.  Entrepreneurial spirit has nothing to do with academic intelligence, with the skill to get the job done  perfectly, but entrepreneurial spirit is a dynamic spirit to turn a challenge into an opportunity.Key words: soft skills, education, entrepreneurship.